Patients' anxiety and hope: predictors and adherence intentions in an acute care context. (18th October 2014) - Legg, Angela M.; Andrews, Sara E.; Huynh, Ho; Ghane, Arezou; Tabuenca, Arnold; Sweeny, Kate
Abstract: Context: Good patient–provider interactions promote satisfaction with health care, adherence to treatment recommendations and improved health. However, little research has examined patients' emotions and how they relate to patients' experiences with health care and their adherence intentions in acute care settings. Objective: This study examined the predictors and consequences of two emotions pertinent to the uncertainty of acute health‐care experiences: anxiety and hopefulness. Design: Patients who arrived at a general surgery clinic for an initial consultation were interviewed before and after the consultation. Prior to the consultation with a physician, patients completed baseline measures of their emotional state. Following the consultation, patients completed measures of understanding of the information provided by the surgeon, perceived control over treatment decisions, adherence intentions and emotional state. Results: Understanding and control predicted less anxiety and greater hopefulness, compared to baseline. Only hopefulness predicted adherence intentions. These relationships remained even after controlling for characteristics of the patients and interactions. Discussion: These findings identify aspects of psychosocial care that are critical for promoting positive (and mitigating negative) emotional states in patients. Even in a brief consultation in a clinic setting, physicians may be able to improve patients' emotional state by promoting a sense of control and clarifying information they convey, and patients' positive emotional states may be critical for raising adherence intentions.